Flouting of Gricean Maxims in Barbie (2023): A Gender-Oriented Pragmatic Analysis (Sastra Inggris UNPAM, 2025)
This study aims to analyze the flouting maxim and the strategies based on the characters’ gender in the movie Barbie (2023) with the use of Grice’s (1975) flouting maxim theory and Cutting’s (2002) strategies of flouting maxim theory. A descriptive qualitative approach was used to examine the flouting maxim and the strategies within the character’s utterance in the movie. The result of the analysis reveals that all four types of flouting maxims are present in the movie with a total of 44 data. Specifically, female characters flouted 12 of the maxims of quantity, 5 of the maxims of quality, 8 of the maxims of relation and 5 of the maxims of manner, while male characters flouted 5 of the maxims of quantity, 6 of the maxim relation, 3 of the maxims of manner, and no data for maxim of quality. The findings reveal that female and male characters tend to flout maxims through irrelevant statements strategy. These results highlight that language use is not only shaped by cooperative principles but also by gendered patterns of communication that influence how speakers express meaning. Overall, the findings suggest that gender differences play a crucial role in determining how conversational maxims are flouted and how specific strategies are employed in interaction.